Rancangan Sistem Otomatis Pada Alat Pembuat Pelet Ikan Berbantu Teknologi Arduino Uno - Princent M.R Simanullang; Moranain Mungkin; Habib Satria (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
Technological developments are currently progressing and developing very rapidly in various ways to facilitate human work and more efficient production in various fields such as fish farming. So the researchers made a design for a fish pellet maker. The purpose of this research was to create a program and design an Arduino-based fish pellet maker automation system. This research method is a design method using ultrasonic sensors as input and autostarting DC motors as output, while the microcontroller used in this study is Arduino Uno with a programming system using Arduino Idea. The results showed that the designed tool worked well, seen from the arduino that controlled the system stably, with an ultrasonic command that would turn on the DC motor automatically when there was movement at a distance of 2 cm, the results of the fish pellet tool could print fish pellets of 4 – 5 mm so it is suitable for adult fish.